Zooplankton Community Structure In The Coastal Waters Of Manjung, Perak And Penang National Park, Penang - Chan, Jiang Wei (2013)
This study was carried out to determine the zooplankton community structure in the coastal waters of Manjung, Perak and Penang National Park (PNP), Penang and the relation between zooplankton community and water quality of the study area. Five sampling stations adjacent to a power plant station (Sultan Azlan Shah Power Station) in Manjung and eight sampling stations surrounding the PNP were selected in this study. Zooplankton and water quality samples were collected monthly from November 2009 to October 2010. Zooplankton samples were collected by horizontal towing with a plankton net (WP-2). A total of 51 zooplankton taxa were recorded in Manjung, with mean abundance and biomass of 3689.96 ± 663.31 ind m-3 and 25.51 ± 0.82 mg m-3 respectively. In PNP, 49 zooplankton taxa was recorded with mean abundance accounted for 1449.99 ± 158.51 ind m-3 and biomass 15.64 ± 0.26 mg m-3. Copepods population was the dominant group recorded in Manjung and PNP with relative abundance amounted for 71.09% and 72.09% respectively. In Manjung, zooplankton biomass and abundance were recorded highest at Station 5 (located at the estuary and mangrove forest) whereas the lowest biomass and abundance was recorded at Station 2 (intake point of the power plant). Meanwhile, in PNP, Station 7 (located at Teluk Kampi with minimal human activities) recorded highest zooplankton abundance and biomass while lowest abundance and biomass was recorded at Station 1 (located at Teluk Bahang and highly impacted by human activities).